Risk, Reward, and Decision-Making in a Rodent Model of Cognitive Aging - Gilbert, Ryan J.; Mitchell, Marci R.; Simon, Nicholas W.; Banuelos, Cristina; Setlow, Barry; Bizon, Jennifer L. (Frontiers in Neuroscience, 2012)
Impaired decision-making in aging can directly impact factors (financial security, quality of healthcare) that are critical to maintaining quality of life and independence at advanced ages. Naturalistic rodent models mimic human aging in other cognitive domains, and afford the opportunity to parse the effects of age on discrete aspects of decision-making in a manner relatively uncontaminated by experiential factors. Young adult (5-7 mo.) and aged (23-25 mo.) male F344 rats were trained on a probability discounting task in which they made discrete-trial choices between a small certain reward (1 food pellet) and a large but uncertain reward (2 food pellets with varying probabilities of delivery ranging from 100% to 0%). Young rats chose the large reward when it was associated with a high probability of delivery and shifted to the smaller but certain reward as probability of the large reward decreased. As a group, aged rats performed comparably to young, but there was significantly greater variance among aged rats. One subgroup of aged rats showed strong preference for the small certain reward. This preference was maintained under conditions in which large reward delivery was certain, suggesting decreased sensitivity to reward magnitude. In contrast, another subgroup of aged rats showed strong preference for the large reward at low probabilities of delivery. Interestingly, this subgroup also showed elevated preference for probabilistic rewards when reward magnitudes were equalized. Previous findings using this same aged study population described strongly attenuated discounting of delayed rewards with age, together suggesting that a subgroup of aged rats may have deficits associated with accounting for costs (i.e., delay, probability). These deficits in cost-accounting were dissociable from the age-related differences in sensitivity to reward magnitude, suggesting that aging influences multiple, distinct neural mechanisms that can impact cost-benefit decision making.